Observation of the Clinical Efficacy of Sanren Laxative Drink in the Treatment of Opioid-induced Constipation - Ding, Panpan; Zha, Mingbao (Journal of Contemporary Medical Practice, 2025)
Objective: To observe the clinical efficacy and safety of Sanren Laxative Drink in the treatment of opioid-induced constipation in patients with cancer pain, to clarify its clinical value, and to provide a theoretical basis for the treatment of opioid-related constipation with traditional Chinese medicine. Methods: A total of 60 patients who met the inclusion criteria in the Department of Oncology of Wuhu Hospital of Traditional Chinese Medicine from December 2023 to December 2024 were randomly divided into control group and treatment group, with 30 cases in each group. The patients in the treatment group were treated with oral Sanren laxative drink on the basis of routine nursing, and the patients in the control group were given oral lactulose solution on the basis of routine nursing for 2 consecutive weeks, and the self-rating scale score, quality of life score and fecal trait score of constipation patients before and after treatment were compared between the two groups. Results: The effective rate of the treatment group was 90%, and that of the control group was 66.67%, and the patients in the treatment group were better than the control group in terms of constipation symptoms, quality of life and fecal characteristics, and the difference was statistically significant(P<0.05). Conclusions: Sanren laxative drink can help improve the fecal properties of OIC patients and assist patients in defecation, and can effectively improve the constipation symptoms and improve the quality of life of patients with cancer pain.